EFEKTIVITAS MODEL TPS (THINK PAIR SHARE) UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN KOMUNIKASI SISWA PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Ivana; Andri Wahyu Wijayadi; Asriana Kibtiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to assess the effectiveness of implementing the Think Pair Share (TPS) cooperative learning model and analyze improvements in student learning outcomes and communication skills on the subject of classification of living things. The study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. Subjects were all seventh-grade students of SMPN III Wonosalam in the 2025/2026 academic year. Learning outcome data were collected through pretests and posttests, while student communication skills were measured through pretests and posttests using questionnaires. Data analysis used a paired sample t-test. The results showed a significant improvement in student learning outcomes and communication skills after implementing the TPS model. The average posttest learning outcome score was 74.96, higher than the pretest score of 45.01. Students' communication skills also improved, with a posttest score of 88.59 compared to the pretest score of 30.93. The significance value (Sig. > 0.05) indicates that the implementation of the TPS model significantly impacted learning outcomes and communication skills. These findings demonstrate that the TPS learning model can improve students' understanding of the material and their communication skills. This model can be an alternative learning strategy that is innovative, interactive, and supports students' activeness and social skills in the learning process.